1959
DOI: 10.1021/ja01517a036
|View full text |Cite
|
Sign up to set email alerts
|

Rauwolfia Alkaloids. XXXI.1 The Synthesis and Activity of Some Reserpine Analogs2

Abstract: due from acetone yielded a second solid product (900 mg.). Two recrystallizations of the second product from alcoholether gave colorless rods (740 mg.), m.p. 265-266°dec., [«]23d -5°( c 1.25, pyr.), 246 µ (e 600).™

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1959
1959
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To characterize the interaction between reserpine and the amine transporter and to use reserpine as a probe of the transporter, it is instructive to compare the effects of a variety of reserpine derivatives. When the structure of reserpine was determined in the 1950s (Dorfman et al, 1954), many derivatives were synthesized and tested for pharmacological effects (Lucas et al, 1959). Kirshner (1965) tried some of these compounds on isolated chromaffin vesicles and reported that their effectiveness as inhibitors of norepinephrine uptake correlated with their catecholamine-depleting potency in vivo.…”
mentioning
confidence: 99%
“…To characterize the interaction between reserpine and the amine transporter and to use reserpine as a probe of the transporter, it is instructive to compare the effects of a variety of reserpine derivatives. When the structure of reserpine was determined in the 1950s (Dorfman et al, 1954), many derivatives were synthesized and tested for pharmacological effects (Lucas et al, 1959). Kirshner (1965) tried some of these compounds on isolated chromaffin vesicles and reported that their effectiveness as inhibitors of norepinephrine uptake correlated with their catecholamine-depleting potency in vivo.…”
mentioning
confidence: 99%
“…Since there are only three such interactions which are due to the methyl groups for XXIV, interaction with an electrophilic center may occur primarily in this somewhat less hindered conformational form. Finally, the glycolate esters of 1,2,2,6,6-pentamethyl- 4-piperidinol (VII), which are virtually devoid of psychotogenic activity, can be seen to have a highly hindered amino nitrogen. An approaching electrophilic center would be subjected to four 1,3-diaxial nonbonded interactions in each of the two possible…”
Section: XVIImentioning
confidence: 99%
“…A series of chemical modifications were made by replacing different organic acids at the trimethoxybenzoic‐acid portion of reserpine (6). As a result, a new substance was found which had the cardiovascular effects of reserpine, yet had minimal sedating activity.…”
mentioning
confidence: 99%